-6(x+1)-14=26+8

Simple and best practice solution for -6(x+1)-14=26+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+1)-14=26+8 equation:


Simplifying
-6(x + 1) + -14 = 26 + 8

Reorder the terms:
-6(1 + x) + -14 = 26 + 8
(1 * -6 + x * -6) + -14 = 26 + 8
(-6 + -6x) + -14 = 26 + 8

Reorder the terms:
-6 + -14 + -6x = 26 + 8

Combine like terms: -6 + -14 = -20
-20 + -6x = 26 + 8

Combine like terms: 26 + 8 = 34
-20 + -6x = 34

Solving
-20 + -6x = 34

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -6x = 34 + 20

Combine like terms: -20 + 20 = 0
0 + -6x = 34 + 20
-6x = 34 + 20

Combine like terms: 34 + 20 = 54
-6x = 54

Divide each side by '-6'.
x = -9

Simplifying
x = -9

See similar equations:

| -6+4y=3 | | 12(x-9)=-8-4 | | 3(5y-6)=9y | | 31y=5(6y-3) | | -5=3m+1 | | (x)(y^3)/x | | -2-9=6x+6-5x | | 0.77+0.31t=3.2t-0.41 | | x/33=-49+25 | | -4x-4x=61-5 | | -3+2b=-9 | | 5-13=z/-9 | | 1+1/(14s) | | 14/9+1/8t=2 | | 4w-16w=108 | | -2+18=m-7 | | x-7=-4+5 | | 3+25x=5(5x+2) | | y=1+(x+2)(x+1)+x | | 25x+6-28x=3-9 | | 24x+8-28x=3+7 | | 22,000-16,000/12x=1000 | | 49y=3(16y+146) | | 5.3+1.1n=2.22 | | 3x+12=3x+4 | | 2x=4-(-14) | | 3w-10w=-21 | | 0.13b+0.21(4b-50)=9 | | 5s=2/3 | | 14a=-10-13a | | x=-123/11 | | -10x=-8x-6 |

Equations solver categories